Validity and Reliability Testing of Indonesian 4-Item Growth Mindset Scale among University Students - Halima Halima; Rita Eka Izzaty; Neni Trinovita; Aqidatul Izzah; Hasfi Putraza Hikmat; Muhammad Haikal Rizqi (Journal An-Nafs: Kajian Penelitian Psikologi, 2026)
This study aimed to adapt and evaluate the psychometric properties of the Indonesian version of the 4-item Growth Mindset Scale in a university student population. A total of 217 undergraduate and graduate students participated in the field testing. Construct validity was examined using confirmatory factor analysis (CFA) with the MLR estimator. The results indicated an excellent model fit (CFI = 0.999, TLI = 0.996, RMSEA = 0.032, SRMR = 0.00797), supporting unidimensional representation of the growth mindset construct consistent with the implicit theories of intelligence framework. All items demonstrated significant loadings, supporting the proposed one-factor measurement model, including the two fixed-mindset items, which showed relatively high standardized loadings. Internal reliability was strong (Cronbach’s alpha = 0.785; stratified alpha = 0.8207). These findings indicate that the Indonesian 4-item version demonstrates satisfactory structural validity and internal consistency, while providing a concise instrument suitable for research and academic assessment. This instrument has the potential to serve as an efficient measure for mapping students’ mindset beliefs and evaluating psychological interventions in higher education settings.